2008
DOI: 10.1016/j.mechmat.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Lattice models of polycrystalline microstructures: A quantitative approach

Abstract: This paper addresses the issue of creating a lattice model suitable for design purposes and capable of quantitative estimates of the mechanical properties of a disordered microstructure. The lack of resemblance between idealized lattice models and real materials has limited these models to the realm of qualitative analysis. Two procedures based on the same methodology are presented in the two-dimensional case to achieve the rigorous mapping of the geometrical and the elastic properties of a disordered polycrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Likewise, for investigating the mechanical responses of other materials, e.g. concrete and polymers, lattice models and discrete networks are often applied (Lilliu and Van Mier, 2003;Cusatis et al, 2003;Ostoja-Starzewski and Wang, 2006;Rinaldi et al, 2008;Kim and Buttlar, 2009;Zhao, 2012). The advantage of discrete models is that they naturally incorporate discrete phenomena occurring in meso-and microstructures of many materials.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, for investigating the mechanical responses of other materials, e.g. concrete and polymers, lattice models and discrete networks are often applied (Lilliu and Van Mier, 2003;Cusatis et al, 2003;Ostoja-Starzewski and Wang, 2006;Rinaldi et al, 2008;Kim and Buttlar, 2009;Zhao, 2012). The advantage of discrete models is that they naturally incorporate discrete phenomena occurring in meso-and microstructures of many materials.…”
Section: Introductionmentioning
confidence: 99%
“…else → sum truss node by adding 1 to the weight factor of triangle t if no internal sampling node in triangle t is selected yet → select truss node i as internal sampling node -Partition f c,s and K c,s , solve system and update solution according to Equation (14) energy is exact, but accepting some error. However, for two-dimensional structural lattice models with only nearest neighbor interactions such as the example considered in this study, the computational cost of the exact method remains acceptable as will be shown in Section 3.…”
Section: Determine Sampling Nodes Per Triangle Based On the Location mentioning
confidence: 99%
“…Das et al [41] coupled finite elements and cellular automata (CAFE) and showed the potential for microstructural and multiscale analysis of heterogeneous and polycrystalline materials. Also lattice models for quantitative estimates of the mechanical properties of polycrystalline microstructures and their damage have been reported [42]. The application and advantages of peridynamics for modelling crack initiation, propagation and fragmentation in polycrystalline ceramics are discussed in [36].…”
Section: Introductionmentioning
confidence: 99%